Sewage sludge and its agricultural potential (Research, Society and Development, 2022)
The sewage consists of the water used in daily activities, used for washing clothes or dishes, in the shower, in the toilet flushing or in the sink. This waste water contains impurities, consisting of a mixture of debris, food scraps, detergents, urine, feces and other substances.When thrown directly into the environment, it generates a strong and fetid odor, in addition to containing harmful bacteria, causing diseases. When properly treated, sludge is called biosolid, and its agroforestry reuse can be an attractive alternative. Thus, the present study aims to identify the biosolid, characterize the treatment process and the composition of the material, report its utilities associated with agriculture and recovery of degraded areas, as well as regulations and legislation in force regarding this residue. The work was carried out through a bibliographic survey that brings together relevant subjects about biosolids, characteristics of biosolids, sewage sludge, use in agriculture, in order to provide a more enlightening and relevant knowledge for the scientific community of ​​sewage sludge treatment area, converting it into biosolid, its characterization and application in agriculture in the most varied aspects.